2010
DOI: 10.3174/ajnr.a2219
|View full text |Cite
|
Sign up to set email alerts
|

Functional MR Imaging in Patients with Carotid Artery Stenosis before and after Revascularization

Abstract: BACKGROUND AND PURPOSE:Significant extracranial stenosis of the ICA is a known risk factor for future stroke and it has been shown that revascularization reduces the risk of future stroke. We applied BOLD fMRI in patients with carotid artery stenosis before and after CEA. Our purpose was to determine whether fMRI is able to demonstrate impaired CVR and to identify patient parameters that are associated with postoperative changes of cerebral hemodynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…38,39 The cellular components of the observed FA or Fc increases are still unknown. They can be attributed to increased vasodilation and blood flow, improved neurovascular reactivity, 40 neural plasticity, 41 and/or remyelination 42 as suggested by MR spectroscopic studies.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 The cellular components of the observed FA or Fc increases are still unknown. They can be attributed to increased vasodilation and blood flow, improved neurovascular reactivity, 40 neural plasticity, 41 and/or remyelination 42 as suggested by MR spectroscopic studies.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the neuropsychological measures and most disrupted FC did not change obviously after statistical adjustments. The strengthened FC neighbor to some disrupted areas at 3 months after CAS may be attributable to restored perfusion and vasomotor reactivity, 20 enhanced axonal transport, and/or functional plasticity of already existing pathways. A study with a larger population and longer observation is needed to determine whether cognitive impairment can be enhanced after CAS and whether the increased brain connectivity may correlate with cognitive improvement.…”
Section: Discussionmentioning
confidence: 99%
“…19 Nevertheless, it has not been studied whether complementary DTI and fcMRI may detect microstructural and functional alteration of neural networks in severe asymptomatic carotid stenosis and after carotid revascularization. 20 In this work, we investigated neuropsychological performance, DTI, and fcMRI in 17 consecutive patients with severe asymptomatic carotid stenosis and compared them with 26 healthy subjects. To our knowledge, this is the first study to demonstrate the disconnections of structural and functional connectivity in correlation with cognitive impairments in patients with severe asymptomatic carotid stenosis.…”
mentioning
confidence: 99%
“…Previous studies suggested that the delayed and reduced magnitude of the BOLD response might indicate the severity of compromised hemodynamics in patients with cerebral ischemic diseases. [18,19] A most recent report observed BOLD responses to specific stimulation in patients with MMD before and after revascularization, and found a predicator for postoperative outcomes, suggesting the feasibility of using BOLD-fMRI for individualized assessment of cerebral hemodynamic impairment and hemodynamic improvement after revascularization in patients with MMD. [20] ASL is another promising technology for cerebral hemodynamics assessment in perioperative management of MMD.…”
Section: Discussionmentioning
confidence: 99%